PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI BERBENTUK FLIP CHART PADA MATERI JAMUR UNTUK SISWA SMA KELAS X - Yulia Ratna Sari; Yoko Masnarivan (Jurnal Bionatural, 2026)
The low percentage of students achieving mastery in test scores regarding the topic of fungi indicates that this subject matter is difficult for students to comprehend; furthermore, a lack of learning resources and supporting facilities for instruction contributes to these low scores. An effective strategy for teachers to address this issue is the use of instructional media, specifically a flip chart. This medium was designed using Adobe Photoshop, resulting in a printed product. The objectives of this study were to develop a biology flip chart on the topic of fungi, assess its feasibility, and determine teacher and student perceptions of the medium. This study employed Research and Development (R&D) methodology using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The final product is a flip chart on fungi. A small-group trial was conducted at SMA N 1 Solok Selatan with nine students from Phase E. Data collection instruments included both open-ended and closed-ended questionnaires, yielding both quantitative and qualitative data. Validation by the media expert resulted in a score of 62 (77.5%), categorized as "Very Good," while the subject matter expert gave a score of 57 (89.1%), also categorized as "Very Good." The small-group trial yielded a score of 547 (95%), categorized as "Very Good." Teacher perception assessments resulted in a score of 117 (94.1%), categorized as "Very Good." The study concludes that the biology flip chart on fungi is suitable for use in classroom instruction and as a resource for independent student learning. Any shortcomings in this medium can be addressed in future relevant development studies.